Meaning and Pragmatism: the Violations of Maxims in Truth Analysis in the TV Series Lie to Me (2010) - Vika, Regina (UI Scholars Hub, 2013)
Grice proposed the Cooperative Principle, which contains four maxims, as an element in communication. When the four maxims is violated, it means that the speaker has did something to create a condition, particularly in crime investigation. The truth condition, which has relation to lie, is frequently happen in people’s life. Lie can be studied pragmatically within the relevance theory. The focus of this study is to analyze the existence of which maxims may be violated in a lie. The study on the characters in TV series Lie to Me shows that each character violates certain maxims in the same time. The reason for selecting Lie to Me, there are various ways and reasons to violate the maxims. The finding of this study that one from four maxims is rarely violated because of a possibility reason. However, it cannot be justified that people are lying means they feel guilty toward crime action. Also, it can be helpful to understand what is the Cooperative Principle theory for linguistic learners.